Fractographic characterization of Al2O3p particulates reinforced Al2014 alloy composites subjected to tensile loading (Fracture and Structural Integrity, 2021)
In the current investigation, efforts are being made to produce an Al2014-Al2O3p composite with variable particle size of 88 mm by liquid stir casting route. 9, 12 and 15 weight proportions of Al2O3p were added to the Al2014 base alloy. By using SEM and EDS testing, microstructural studies have been conducted. Al2014-9, 12 and 15 weight proportion of Al2O3p composites mechanical behavior is determined in line with ASTM standards. Electron microscopic images showed that alumina (Al2O3p) particles are dispersed uniformly within the Al2014 composite matrix. EDS study confirmed the proximity of Al and O elements to composites reinforced by Al2O3p. It is also found that Al2014-Al2O3p composite hardness, UTS, and yield strength are improved by the addition of 9, 12 and 15 weight proportion of Al2O3p. Due to the addition of alumina particles in the Al2014 matrix alloy, the ductility of the produced composites decreases. Tensile fractography is performed using SEM to consider the mechanisms for failure.
Keywords: Al2014 alloy; Al2O3p; Mechanical Behavior; Fractography